2023
DOI: 10.3389/fphys.2023.1248999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term water velocity stimulation on the biochemical and transcriptional responses of grass carp (Ctenopharyngodon idellus)

Tingting Shu,
Yan Chen,
Kan Xiao
et al.

Abstract: Since 2011, ecological operation trials of the Three Gorges Reservoir (TGR) have been continuously conducted to improve the spawning quantity of the four major Chinese carp species below the Gezhouba Dam. In particular, exploring the effects of short-term water velocity stimulation on ovarian development in grass carp (Ctenopharyngodon idellus) is essential to understand the response of natural reproduction to ecological flows. We performed ovary histology analysis and biochemical assays among individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Water stimulation is crucial for some fish species, as it can stimulate ovarian development, spawning and fertilization (Li et al, 2020;Chen et al, 2021;Shu et al, 2023). This study found that water stimulation slowed down the development of ovary.…”
Section: Fshβ and Lhβ Gene Expression And Content Changesmentioning
confidence: 73%
“…Water stimulation is crucial for some fish species, as it can stimulate ovarian development, spawning and fertilization (Li et al, 2020;Chen et al, 2021;Shu et al, 2023). This study found that water stimulation slowed down the development of ovary.…”
Section: Fshβ and Lhβ Gene Expression And Content Changesmentioning
confidence: 73%